IMPLEMENTASI KEBIJAKAN PEMERINTAH DAERAH DALAM PENANGGULANGAN PENYAKIT HIV/AIDS DI KOTA PALU - Meluwu, Daniel Silinggawe (Katalogis, 2013)
This study aimed at finding out the implementation of the Regional Government Policy of the coping with HIV/AIDS Disease in Palu City. This study was a qualitative study. Informant of this study consisted of the commission of coping with AIDS of Palu city, Health Office Staff, Indonesia Family Planning Club and the people who are infected by HIV/AIDS in Palu city. Informant was determined purposively. Method of data collection was done through interview, observation, study of reference and documents. Technique of data analysis entailed data reduction, data presentation and drawing conclusion. The result of study showed that the implementation of the coping with HIV/AIDS policy in Palu city had not yet worked well as seen from all aspects investigated: communication, recourses, disposition, and bureaucracy structure; these aspects were not well implemented maximally. The communication was only conducted through mass media/electronic and when the activity was being taken place; it was not done clearly and consistenly with related party. The recources had low ability in communicating the policy and budget recource compounded with limited facility and infrastructures. The disposition also did not show good result. Although the policy implementers demonstrated responsive and supportive manner, in the implementation of the policy they had not performed maximally. In relation to bureaucracy structure, the implementers had not yet possessed good understanding toward their task of the policy as well as no guidance of the implementation to the policy, that inhibiting the policy implementation of the coping with HIV/AID disease in Palu city.